Treatment journey in rheumatoid arthritis with biosimilars: from better access to good disease control through cost savings and prevention of nocebo effects - Bruno Fautrel; Josef S Smolen; Fabrizio Benedetti; Roberto Caporali; Thomas Doerner; Burkhard Pieper; Minjun Jang (RMD Open)
Early diagnosis and treatment of rheumatoid arthritis (RA) are of critical importance to halt the progression of the disease. Optimal use of advanced imaging techniques or biomarkers may facilitate early diagnosis of RA. Even though many disease-modifying anti-rheumatic drugs (DMARDs) are available for RA treatment, biological DMARDs (bDMARDs) offer expanding therapeutic options and good outcomes in patients with RA who do not have a sufficient response to conventional synthetic DMARDs. However, high costs of bDMARDs have limited patient access to optimised disease management and increased the cost burden for healthcare systems. The advent of biosimilars led to significant cost savings driven by price competition among the reference products, which could be beneficial for healthcare systems. Healthcare provider (HCP)–patient communication and informed shared decision-making are crucial to prevent the occurrence of a nocebo effect, which results from negative perceptions that patients may have and could lead to less effective outcomes. Research has demonstrated that effective communication between HCPs and patients utilising positive framing can improve acceptance by patients to be initiated on or switched to a biosimilar and can help to integrate biosimilars into routine clinical practice to maximise benefits for patients with RA.